Nonhelical Helicobacter pylori Mutants Show Altered Gland Colonization and Elicit Less Gastric Pathology than Helical Bacteria during Chronic Infection - Martínez, Laura E. (Infect Immun, 2019)
Half of all humans harbor Helicobacter pylori in their stomachs. Helical cell shape is thought to facilitate H. pylori’s ability to bore into the protective mucus layer in a corkscrew-like motion, thereby enhancing colonization of the stomach. H. pylori cell shape mutants show impaired colonization of the mouse stomach, highlighting the importance of cell shape in infection. To gain a deeper understanding of how helical cell morphology promotes host colonization by H. pylori, we used three-dimensional confocal microscopy to visualize the clinical isolate PMSS1 and an isogenic straight-rod mutant (Δcsd6) within thick longitudinal mouse stomach sections. We also performed volumetric image analysis to quantify the number of bacteria residing within corpus and antral glands in addition to measuring total CFU. We found that straight rods show attenuation during acute colonization of the stomach (1 day or 1 week postinfection) as measured by total CFU. Our quantitative imaging revealed that wild-type bacteria extensively colonized antral glands at 1 week postinfection, while csd6 mutants showed variable colonization of the antrum at this time point. During chronic infection (1 or 3 months postinfection), total CFU were highly variable but similar for wild-type and straight rods. Both wild-type and straight rods persisted and expanded in corpus glands during chronic infection. However, the straight rods showed reduced inflammation and disease progression. Thus, helical cell shape contributes to tissue interactions that promote inflammation during chronic infection, in addition to facilitating niche acquisition during acute infection.